Armenian and Azerbaijan Diasporic Nationalism Manifestation in Nagorno-Karabakh - Rahayu Agustina Hamonangan Simangunsong; Ani W. Soetjipto (Intermestic: Journal of International Studies, 2022)
This article aims to see how the diasporas’ nationalist ideas are manifested in the homelands’ conflict through a comparative case study of the Armenian and Azerbaijani diasporic nationalism in the Nagorno-Karabakh Conflict. Factors affecting the efficacy of diasporic activity from Shain & Barth (2003) is used as the conceptual framework within which the comparison is conducted. The result of this case study indicates that the manifestation of Armenian diasporic nationalism tends to be radical while Azerbaijani diasporic nationalism tends to be moderate. In conclusion, this case study finds that there are various aspects other than nationalism that influence the dynamics of diaspora activism and need deeper investigation, for example by integrating approaches that are sensitive to the experiences of marginalized groups such as feminism and postcolonialism in the diaspora studies.Keywords: diaspora, diasporic nationalism, international relations